2003
DOI: 10.1038/sj.cgt.7700563
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells reconstituted with human telomerase gene induce potent cytotoxic T-cell response against different types of tumors

Abstract: Human telomerase reverse transcriptase (hTERT) is the catalytic component of a functional telomerase complex, which is important in maintaining cell immortality. In most normal human adult cells, the expression of telomerase is very low and/or transient. In contrast, almost 90% of human tumors express a relatively high level of telomerase implying the possibility of using hTERT as a universal candidate tumor antigen. In this study, we show that human monocyte-derived dendritic cells (DCs) lack telomerase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Transcriptional upregulation of the hTERT catalytic unit gene expression has been observed with greater than 90% of human cancers. 25,39 This ubiquitous expression in tumors has made telomerase a very attractive target for several types of therapeutic modalities for cancer including immunotherapy, [40][41][42][43] gene therapy [32][33][34][35] and, as described in this report, oncolytic virotherapy. We and others have demonstrated the safety and efficacy of intratumoral delivery of replication-deficient, recombinant adenoviruses in which the hTERT promoter was used to drive either proapoptotic genes [32][33][34] or HSV-TK gene in combination with GCV.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional upregulation of the hTERT catalytic unit gene expression has been observed with greater than 90% of human cancers. 25,39 This ubiquitous expression in tumors has made telomerase a very attractive target for several types of therapeutic modalities for cancer including immunotherapy, [40][41][42][43] gene therapy [32][33][34][35] and, as described in this report, oncolytic virotherapy. We and others have demonstrated the safety and efficacy of intratumoral delivery of replication-deficient, recombinant adenoviruses in which the hTERT promoter was used to drive either proapoptotic genes [32][33][34] or HSV-TK gene in combination with GCV.…”
Section: Discussionmentioning
confidence: 99%
“…53 The widespread expression of telomerase in tumors indicated that peptide fragments of hTERT could serve as tumor-specific antigens and this has been confirmed by some recent reports. 54,55 Therefore, another part of the antitumor immunity may be derived from the anti-hTERT CTL responses. Taken together, we showed that the mutant TNF-a with mutations at D142N and A144R has less in vitro cytotoxic effect, but maintains its functional effect in the stimulation of T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This produced immortalized DCs that were shown to induce a cytotoxic T cell response both in vitro and in vivo. 128,129 Inhibition of apoptosis The major pathway targeted by these cytokines affecting apoptosis is through the anti-apoptotic Bcl-2 protein. Studies have shown IL-2, IL-7, and IL-15 all to decrease apoptosis and enhance survival of both NK and CD8 C T cells by upregulation of Bcl-2.…”
Section: Underlying Mechanisms That Increase Immune Cell Longevitymentioning
confidence: 99%